Rat model for dominant dystrophic epidermolysis bullosa: glycine substitution reduces collagen VII stability and shows gene-dosage effect - Nyström, Alexander; Buttgereit, Jens; Bader, Michael; Shmidt, Tatiana; Özcelik, Cemil; Haußer-Siller, Ingrid; Bruckner-Tuderman, Leena; Kern, Johannes S. (PLOS ONE, 2013)
Dystrophic epidermolysis bullosa, a severely disabling hereditary skin fragility disorder, is caused by mutations in the gene coding for collagen VII, a specialized adhesion component of the dermal-epidermal junction zone. Both recessive and dominant forms are known; the latter account for about 40% of cases. Patients with dominant dystrophic epidermolysis bullosa exhibit a spectrum of symptoms ranging from mild localized to generalized skin manifestations. Individuals with the same mutation can display substantial phenotypic variance, emphasizing the role of modifying genes in this disorder. The etiology of dystrophic epidermolysis bullosa has been known for around two decades; however, important pathogenetic questions such as involvement of modifier genes remain unanswered and a causative therapy has yet to be developed. Much of the failure to make progress in these areas is due to the lack of suitable animal models that capture all aspects of this complex monogenetic disorder. Here, we report the first rat model of dominant dystrophic epidermolysis bullosa. Affected rats carry a spontaneous glycine to aspartic acid substitution, p.G1867D, within the main structural domain of collagen VII. This confers dominant-negative interference of protein folding and decreases the stability of mutant collagen VII molecules and their polymers, the anchoring fibrils. The phenotype comprises fragile and blister-prone skin, scarring and nail dystrophy. The model recapitulates all signs of the human disease with complete penetrance. Homozygous carriers of the mutation are more severely affected than heterozygous ones, demonstrating for the first time a gene-dosage effect of mutated alleles in dystrophic epidermolysis bullosa. This novel viable and workable animal model for dominant dystrophic epidermolysis bullosa will be valuable for addressing molecular disease mechanisms, effects of modifying genes, and development of novel molecular therapies for patients with dominantly transmitted skin disease.